EXPLORING FACTORS AFFECTING EFL LEARNERS’ SPEAKING PERFORMANCE: FROM THEORIES INTO PRACTICES - Irma Wahyuni (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2022)
Theoretically, the ultimate goal of any language learning including EFL (English as a Foreign Language) is to communicate, that is toexchange ideas, knowledge, and information. Among the fourlanguage skills the learners pursue in their language learning, theyoften value speaking more than the other skills – reading, writing,and listening. Some studies show that despite learners’ strong motivation to learn and practice speaking in English, on manyoccasions they turn out to stay silent (instead of saying passive) rather than struggle to make any attempt to speak words. Exploringany possible factors causing this phenomenon to happen is of agreat value for teaching practitioners as it is commonly believedthat speaking is interconnected with other skills. Therefore, thedevelopment in speaking is likely resulted in the development ofthe other language skills. In relation to the above issue, hence, this short article tries to examine factors affecting EFL learners’ speaking performance and to identify some feasible ways of coping with the demotivating factors of the speaking performance. Drawing from some literature reviews it was found that EFL learners’ speaking performance may stem from three major aspects, namely linguistics, socio-cultural, and affective factors which includes motivation and personality aspects such as anxiety, selfesteem, inhibition, risk-taking, empathy, and extroversion